Exploring Buginese Students’ English Pronunciation Difficulties in Poleang Selatan - Nasril, Nasril; Artini, Luh Putu; Adnyani, Ni Putu (Institut Agama Islam Negeri Kendari, 2024)
Most students in Indonesia still need help with English pronunciation and speaking due to the interference of local languages in students’ oral English production. This study aims to describe the interference of the Bugis language, a local language spoken in Southeast Sulawesi, on students’ English speaking skills. The data for this research were collected from 24 seventh-grade students at a junior high school in Poleang Selatan, Southeast Sulawesi, Indonesia. The participants included 10 males and 14 females. The study seeks to examine how the Bugis language influences students’ oral English during speaking activities in the classroom. This research employed a descriptive qualitative approach, using an interactive model for data analysis. The process included analyzing, categorizing, coding, displaying data, and drawing conclusions. The results revealed that most students made numerous pronunciation errors with English vowel sounds such as /ʌ/, /ɪ/, /i:/, /u:/, /ɒ/, /ə/, /ӕ/, and /ʊ/, which were influenced by the Bugis language. Consequently, students tended to rely on guessing based on their prior knowledge of their native language.